Eldrimner Mathantverk - Haglund, Karin (2017)
Although mass production of undifferentiated commodities dominates the market for food products, a shift has turned consumers’ interests towards alternative food chains with a focus on quality attributes, origin and a stronger control and guarantee. But as the variety of food products expands, consumers require more information in their purchase situations. Several of the attributes of food items, such as origin, quality or socially constructed concepts as authentic and traditional, are difficult for the customers to identify before consumption. The brand’s function to transfer such quality attributes is one way to decrease the customer’s informational problems and to raise the producers’ differentiability.